1982
DOI: 10.1007/bf01308124
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diagnosis of massive hepatic infarction by computed tomography

Abstract: A patient is presented with a postpartum hepatic artery thrombosis in association with presumed fibromuscular hyperplasia. Massive hepatic infarction developed characterized clinically by fever, coma, ascites, ileus, jaundice, and renal failure; and biochemically by markedly elevated SGOT and SGPT, alkaline phosphatase, total bilirubin levels, and decreased thromboplastin time. The diagnosis was made in vivo by computed tomography (CT). Angiography revealed thrombotic occlusion of the hepatic artery in associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Six pregnancies had complete HELLP and PE ([15,19,22,23] and our case 1). One had incomplete HELLP and PE [18], nine had complete HELLP and no PE [7,14,16,17,19,21–23,26] and five pregnancies had incomplete HELLP and no PE ([10,11] and our cases 2, 3 and 4). Only 33% of patients had PE, and complete HELLP occurred in 71% of the pregnancies.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Six pregnancies had complete HELLP and PE ([15,19,22,23] and our case 1). One had incomplete HELLP and PE [18], nine had complete HELLP and no PE [7,14,16,17,19,21–23,26] and five pregnancies had incomplete HELLP and no PE ([10,11] and our cases 2, 3 and 4). Only 33% of patients had PE, and complete HELLP occurred in 71% of the pregnancies.…”
Section: Resultsmentioning
confidence: 94%
“…A review of the English language literature revealed additional 26 cases of hepatic infarction during pregnancies in 24 women [7–26]. The description herein includes both these 24 women and our four patients, a total of 30 pregnancies in 28 women.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several causes of puerperal ascites have been described in the literature, all with a clinical picture similar to that of the spontaneous rupture of the bladder. One case of postpartum hepatic artery thrombosis has been described by Damman et al in a patient presenting with fever, coma, ascites, ileus, jaundice and renal failure after delivery [18]. The impaired liver function suggested the hepatic origin of the clinical pictures.…”
Section: Discussionmentioning
confidence: 97%
“…Sonographisch soll in der akuten Phase eines Leberinfarktes lediglich eine Organvergrößerung imponieren (3), so daß in diesem Stadium eine wesentliche diagnostische Bedeutung verneint wird. In der Remissionsphase können Leberinfarkte jedoch eindeutig erfaßt werden (3). In unserem Fall war der Literatur…”
Section: Fallberichtunclassified